Differing phylogeographic patterns within the Indo‐West Pacific mangrove genus Xylocarpus (Meliaceae). (27th December 2017) - Guo, Zixiao; Guo, Wuxia; Wu, Haidan; Fang, Xiaoting; Ng, Wei Lun; Shi, Xianggang; Liu, Ying; Huang, Zhicheng; Li, Weixi; Gan, Lu; He, Sining; Zhong, Cairong; et al.
Abstract: Aim: The genus Xylocarpus contains two mangrove species, X. granatum and X. moluccensis, and a rare non‐mangrove, X. rumphii . The two mangrove species are ideal models to study the biogeography of coastal plants with a unique dispersal ability, that is via buoyant propagules. We constructed the phylogeny of Xylocarpus and its relatives and determined the population structures of the two mangrove species. We aimed to elucidate the roles of continental drift and long‐distance dispersal (LDD) in shaping the present‐day distribution of Xylocarpus  and to determine the factors affecting the patterns of population differentiation. Location: The Indo‐West Pacific (IWP) region. Methods: Thirty populations of X. granatum, 15 of X. moluccensis and four of X. rumphii were sampled across the IWP region. Five chloroplast DNA intergenic spacers were sequenced for Xylocarpus and outgroup species to determine divergence times. The genetic diversity, divergence and structure of the two mangrove species were further analysed using five nuclear and two chloroplast DNA loci. Migrations between oceanic regions were estimated. Results: The genus Xylocarpus diverged from its sister genus Carapa approximately 19.4 Ma. The populations of X. granatum differentiated into three groups, with genetic breaks present across the Malay Peninsula and Wallacea, whereas X. moluccensis populations differentiated into two groups, with a genetic break present only across the Malay Peninsula. Migration was also observed between populations of the Southeast Asian and Australasian regions in X. moluccensis but not in X. granatum . Main conclusion: Since Xylocarpus originated after the breakup of Gondwana and subsequent plate motions, its current distribution range should have been facilitated by present‐day LDD instead of past continental drift. Despite the capacity of LDD, the presence of differing population structures across land barriers (the Sunda and Sahul Shelves) and ocean currents indicated differential limitations in the dispersal capabilities of X. granatum and X. moluccensis .